CHARITY AS THE AESTHETIC ACTIVITY - Мокляк, Л. І. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article analyzes the charity as a form of aesthetic activity in the context of social and cultural transformations of contemporary Ukrainian society.